Anticancer and Antioxidant Activity of Water-Soluble Polysaccharides from Ganoderma aff. australe against Human Osteosarcoma Cells (2022)
ABSTRACT: Wild mushrooms have gained great importance for being a source of biologically active compounds. In this work, we evaluate the anticancer and antioxidant activity of a water-soluble crude polysaccharide extract isolated from the fruiting bodies of the Ganoderma aff. australe (GACP). This mushroom was collected in San Mateo (Boyacá, Colombia) and identified based on macroscopic and microscopic characterization. GACP was characterized by UV–Vis spectroscopy, Fourier-transform infrared spectroscopy, high-performance liquid chromatography–diode array detector, and nuclear magnetic resonance. The antiradical and antioxidant activity were evaluated by different methods and its anticancer activity was verified in the osteosarcoma MG-63 human cell line. Chemical and spectroscopic analysis indicated that GACP consisted of β-D-Glcp-(1→, →3)-β-D-Glcp-(1→ and α-D-Glcp-(1→ residues. The results of the biological activity showed that GACP exhibited high antioxidant activity in the different methods and models studied. Moreover, the results showed that GACP impaired cell viability (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay) and cell proliferation (clonogenic assay) in a dose–response manner on MG-63 cells. The findings of this work promote the use of mushroom-derived compounds as anticancer and antioxidant agents for potential use in the pharmaceutical and food industries